Supply of Aspect Tourism Effect on Travelling Interest - Herlin Herlin; Ida Ayu Made Er Meytha Gayatri (Fakultas Ekonomi, Universitas Bangka Belitung, 2020)
Purpose of this study aims to examine the effect supply aspect tourism on travelling interest to Tikus Island in Bengkulu Province. Supply aspect tourism consisting of attraction, accessible, amenities and ancillary. Sampling method in this study is accidental sampling with 240 respondents. Data collection method in this study uses quantitative data which is carried out by distributing questionnaires. Multiple regression analysis applied to test the hypotheses using SPSS application. Findings showed that attraction and accessible have positive effect on travelling interest. Meanwhile, amenities and ancillary do not affect travelling interest. The supply of aspect tourism in Tikus Island can contribute to the Regional Original Income (PAD) of Bengkulu Province, the local government of Bengkulu should be able to pay more attention based on this findings.